Developing Story Writing Skills with Fourth Grade Students' Mind Mapping Method - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2020)
The aim of this study is to develop story-writing skills by using the mind map method of fourth grade primary school students. In this respect, the study was designed as a mixed-method research in which quantitative and qualitative research is used together. Quantitative dimension of the study pre-test the post-test was designed as qualitative dimension action study with semi-experimental model. The sample of the study is composed of three classes at the fourth-grade level of two equal state schools in Mentee district of Mugla province during the fall semester of 2016-2017 academic year. One of the three groups was chosen as the experimental group and two were selected as the control group. Studies have been made to experiment group; writing story with mind map method, to first control group; story-writing-work with homework, to second control group; the study was carried out in line with the Turkish Course curriculum. In the workshop carried out with experimental group, students were given a mind map study during 1 course, story maps and story writing studies during 1 course. The workshop lasted 10 weeks. In the workshop made with the first control group, students were asked to write stories by using the given subjects. No intervention was taken into the second control group. As a result of the study, it was concluded that the mind map method applied to the experiment group was more effective than other workshops.
Keywords: Writing; Story writing; Mind map; Story writing-work; Mixed method